2007
DOI: 10.1111/j.1365-3156.2007.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual inspection and Papanicolau (PAP) smears for cervical cancer screening in Honduras: should PAP smears be abandoned?

Abstract: Summaryobjective To compare visual inspection with acetic acid (VIA) to Papanicolau (PAP) smears in a community setting in a developing nation.methods Women undergoing cervical cancer screening in Honduras received either VIA and PAP smears (VIA ⁄ PAP group) or PAP smears alone (PAP-only group). Local healthcare providers performed PAP screening. A VIA-trained nurse performed VIA exams. All PAP smears were processed in Honduras. PAP smears from the VIA ⁄ PAP group were reviewed in the United States. Women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(32 reference statements)
1
15
1
Order By: Relevance
“…The result of screened-positive women by VIA in this study (7.6%) was higher than that found in Bangladesh (4.8%)14 and in Angola (6.6%),15 but lower than in Kenya (13.9%)16 or in Honduras (14%),17 and it was much lower than found in El Salvador (26.5%),18 or in Thailand (38.1%) 19…”
Section: Discussioncontrasting
confidence: 74%
“…The result of screened-positive women by VIA in this study (7.6%) was higher than that found in Bangladesh (4.8%)14 and in Angola (6.6%),15 but lower than in Kenya (13.9%)16 or in Honduras (14%),17 and it was much lower than found in El Salvador (26.5%),18 or in Thailand (38.1%) 19…”
Section: Discussioncontrasting
confidence: 74%
“…A study in Honduras found that among 339 women who had both VIA and a Pap test, 49 VIA examinations were read as abnormal. 7 Of these, 23 had biopsyproven dysplasia. None of the 23 true positive cases was identified when the Pap tests were read in Honduras and only 4 were identified when the slides were reread in the United States.…”
Section: Effectiveness Of Screening Methodsmentioning
confidence: 98%
“…During our community-based screening and treatment project in Honduras (Perkins, Langrish, Stern, Figueroa, & Simon, 2007) we found that factors including lack of communication infrastructure (telephone, postal services), routine supplies (spatulas, fixative, laboratory dyes), and up-to-date cytopathologist training and certification negatively impacted both Pap smear quality and patient adherence. The impact of these local factors may be important when comparing the cost-effectiveness of Pap smear and VIA screening programs.…”
Section: Introductionmentioning
confidence: 99%